2015
DOI: 10.1080/10803548.2015.1081770
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between circadian rhythm amplitude and stability with sleep quality and sleepiness among shift nurses and health care workers

Abstract: Those whose circadian rhythm amplitude was languid suffered more from sleepiness and those whose circadian stability was flexible had a better sleep. Variables including circadian rhythm stability (flexible/rigid) and amplitude (languid/vigorous) can act as predictive indices in order to employ people in a shift work system so that sleepiness and a drop in quality of sleep are prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 21 publications
5
41
3
2
Order By: Relevance
“…According to the authors, these results may indicate that stress at work and sleepiness are among the factors that affect sleep quality in shift workers. 11 The workers, because they have irregular hours of sleep, are unable to recover for the next day, which compromises their performance at work. 17 However, nurses' health-related behaviors may be influenced by the culture, structure and policies of the organization in which they are employed and by personal factors such as age, sex, marital status, emotional support, general physical health, health perception, perceived benefits or barriers to health, and a sense of confidence in the ability to make changes.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, these results may indicate that stress at work and sleepiness are among the factors that affect sleep quality in shift workers. 11 The workers, because they have irregular hours of sleep, are unable to recover for the next day, which compromises their performance at work. 17 However, nurses' health-related behaviors may be influenced by the culture, structure and policies of the organization in which they are employed and by personal factors such as age, sex, marital status, emotional support, general physical health, health perception, perceived benefits or barriers to health, and a sense of confidence in the ability to make changes.…”
Section: Discussionmentioning
confidence: 99%
“…A random sample survey done by Hsieh and her colleagues in 2011, has the similar findings that 59% of shift nurses ( n = 390) had insomnia (Hsieh et al, ). A study in Iran reported that 83.2% of nurses suffered from poor sleep and approximately 50% had moderate to excessive sleepiness (Jafari Roodbandi et al, ). According to the National Sleep Foundation (), 56% of Americans sleep less than seven to nine hours as recommended during workdays and the average time of sleep of nurses is about five to six hours, less than that of the general population (National Sleep Foundation, ; Geiger‐brown et al, ).…”
Section: Nurses Shift Systems and Sleep Problems For Nursesmentioning
confidence: 99%
“…Shift work has significantly changed nurses' sleep patterns. Between 57% and 83.2% (Jafari Roodbandi, Choobineh, & Daneshvar, 2015;Shao, Chou, Yeh, & Tzeng, 2010) of shift nurses worldwide report sleep problems, including sleep disturbances (Hsieh et al, 2011;Reynolds et al, 2016), sleep deprivation (Kaliyaperumal, Elango, Alagesan, & Santhanakrishanan, 2017), and poor sleep quality (De Martino, Abreu, Barbosa, & Teixeira, 2013;Shao et al, 2010;Shu-Hui, Wen-Chun, Mei-Yen, & Jun-Yu, 2014). Sleep deprivation and sleep disturbances have been associated with fatigue (Hughes & Rogers, 2004), chronic diseases, and reduction in health-related quality of life (Asaoka et al, 2013) in shift nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies which have been conducted on the nurses' sleep were related to the circadian rhythm (15), childcare, home responsibility and leisure time (16), relationship between sleep quality and general health (17), quality of life (QOL) (18), nursing errors (19), traffic accidents (20), hormonal changes (21), and different diseases (22). However, few studies have assessed the underlying factors that affect the sleep quality of nurses, especially the cultural differences that should be noted in this regard (16).…”
Section: Introductionmentioning
confidence: 99%